Auto-Reset Mechanism with GSM Assisted Feature for Temporary Fault and Permanent Fault Trip Conditions in Power System - Jospine, Almaeldoe; Ponniran, Asmarashid (Evolution in Electrical and Electronic Engineering, 2022)
The auto-reclose relay is a critical relay that is used to re-energize a line after it has been tripped by the main protection relay due to a fault. A three-phase power system that distributes power to industrial and home consumers might experience many breakdowns. These failures are caused by a variety of defects that can be either transient or permanent. The power system could be seriously harmed because of these faults. This might disturb the power supply and bring numerous industries connected to the system to a stop. This technology can resolve the problem by automatically sensing the fault and disconnecting the system from the power supply, preventing large-scale damage to the system’s equipment. The system automatically distinguishes between a temporary interruption and a permanent fault and cuts the supply for a short or lengthy period of time as needed. The constructed model contains several limits to make the modeling process easier, and the findings suggest that MATLAB Simulink software can be used to simulate the scheme for the project. If the tripping occurs, the Global System for Mobile Communication (GSM) system will send an SMS to the operators of the power system. If the system detects a fault, it will cause the system to trip or interrupt and send an SMS to the operators.